Protein p53 and inducer-mediated erythroleukemia cell commitment to terminal cell division. - Shen, D W (1983)
Inducer-mediated murine erythroleukemia cell (MELC) differentiation provides a model for examining factors determining terminal cell differentiation. The nuclear protein, p53, has been implicated as a potential determinant of cell cycle progression and cell differentiation. In this study p53 content and synthesis, during inducer-mediated MELC differentiation, has been examined with monoclonal antibodies to p53. A decrease in p53 synthesis and content was demonstrated during induced differentiation. As determined by cell cycle fractionation, the decrease in p53 is manifest at all stages of the cell cycle. Hemin, which induces globin mRNA accumulation but not terminal cell division, fails to decrease p53 content. A MELC variant resistant to inducer-mediated commitment to terminal cell division also fails to decrease p53 levels in response to inducers. These experiments suggest that p53 is implicated in MELC cell proliferation and that an induced decrease in p53 may be responsible for G1 phase prolongation and terminal G1 arrest.